A Study to Explore the Innovation in Health and Safety of Employees in an Organization - Kaushik, Ridhima (Journal of Advanced Research in Service Management, 2022)
The development or evaluation of an idea in the workplace via research is necessary for the innovation of ideas. Before the researcher will implement an innovation new idea, they will first carry out a number of studies in the work study. Ergonomic injuries, stress, eye strain, workplace aggression, sliding and failing to keep a visitor register are the most prevalent types of problems that employees have while at work. Other typical issues include stress and eye strain. Ensure that the employee’s safety is taken care of at the workplace. The following is a list of methods and strategies that may be used to find an employee’s health and safety: The literature review has been utilized as a technique to develop new ideas for improving the health and safety of employees in the workplace. In this particular study, it was discovered that it also brings. Employees in good employee, A decrease in the cost of accidents, a regulated environment, a rise in profits, a decrease in the work of environment fires and an increase in the potential for job-related innovation. A great number of firms did not adequately protect their employees. It is not only that the worker health and safety has to be refreshed that puts the health and safety of workers in need. A constructive support system that has its roots in the worker power. The work of health and safety in the workplace contributes to the risk of possible risks and the determination of major ways. It gives you the ability to take precautions against the environment in order to protect your employees and the organization as a whole. It is very necessary for businesses to have an environment like this in order to cut down on the costs connected with safety.